A Theory of Providence for Distributive Justice - Rosen, Shlomo Dov (Journal of religious ethics, 2018)
Distributive justice assumes a morally critical judgment of nature, which typically contradicts providential conceptions. Hence, simple conceptions of divine Providence cannot support distributive justice. This essay analyzes and develops a complex strand of theorizing about Providence within Jewish philosophy that is compatible with distributive justice. According to this conception, the actions of divine Providence express different and mutually exclusive considerations of justice. Therefore, the moral value of outcomes is intransitive between the situations of different people. And while each providential action is justified from an ethical perspective, the total outcome is distinct from God's ultimate desire. Human ethics responds to this disparity by redistribution. This conception of Providence also contributes to the additional issue of intergenerational justice through the concomitant idea of life missions. The classical rendering of missions creates problems, however, for distributive justice. I conclude by formulating a conception of life missions that is compatible with both distributive and intergenerational justice.